A visita familiar no contexto do acolhimento institucional de crianças - SILVA, Tamires Santos Rufino e (Universidade Federal do Pará, 2019)
The family visit (VF) should be understood as an important means of bringing people together who, for various reasons, are far apart and / or had difficult relationship. This research aimed to investigate aspects that characterize the family visit in child care institutions in the metropolitan area of Belém. For this, three studies were performed, one quantitative and two qualitative with descriptive and exploratory approaches. The first study aimed to describe general caracteristics of family visit in host institutions in the metropolitan region of Belém. The second study investigated aspects of environmental organization and the preparation of the child before, during and after the visit, considering, therefore, the point of view of the technicians and educators in the surveyed institutions. The third study investigated the family visit as a proximal process, analyzing the interactions occurring among children who were in the child care institutions and the family that visited these infants. In the first study, as the research was done through documentary research, data collection was made exclusively from medical records provided by the institutions surveyed, using two research tools: a characterization form of children and a description of the institution questionnaire. In the second study, the collection data was carried out using semi-structured interviews to identify the perception of technicians and educators about the VF in a particular context. In the third study, data collection was carried out through semi-structured interviews with visitors and the observation of their interactions with the children at the time of visit. The results from the first study indicated that there was a significant statistically association between the condition of the child receive or not the visit with the following variables: the welcoming time (p = 0.034) and the destiny of the child after leaving the institution (p = 0.012). It was verified that there was a significant statistically association between the condition of the child receive or not mother's visit with the following variables: abandonment (p = 0.25) and sexual violence (p = 0.002) as well as with the visit of uncles who abandon (p = 0.001) and sexual violence (p = 0.000). In addition, the results indicate a significant statistically association between the variables to receive community’s visit with the abandonment as a motive of the caring for the child (p = 0.037). In the second study, the data suggest that in the government institution little or no attention has been given for the preparation of the child and for the environment at the moment of the family’s visit while in the non-governmental organization, it was observed a care and great attention to this form of face-to-face and social interaction among members of the same family or community, separated for whatever reason. In the third and last study, it was discussed why and how the visit can constitute an important proximal process in terms of bioecology of human development. Based on four case studies, aspects were analyzed searching to describe the proximal processes observed at different moments of the family visit. The results showed that in all cases there were effects of competence and dysfunction in the proximal relationship between the visitors and the ones who are visited. The studies helped to verify that the family visit (VF) can act as a means to guarantee the right to family and community life for children institutionally accepted, in that it contributes through the quality of interactions held at this time for the preservation of ties relatives. In this sense, it is considered that the family visit can promote the healthy development of the child even in a often hostile environment, such as host institutions.